CORRELATION ANALYSIS OF ANION AND CATION QUANTITIES IN SOIL WHEN STUDYING SALT TOLERANCE OF LICORICE PLANTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The study revealed patterns of adaptation of the investigated smooth licorice species to moderately and severely saline soils, improvement of soil agronomic conditions, humus enrichment, increased fertility, and above-ground biomass formation. The practical value of the work is in developing scientifically grounded recommendations for sustainable implementation and advancement of licorice planting technologies in soils with moderate salinity levels of 1.3-1.6% and high salinity levels of 1.6-2.5%. In studying the salt tolerance of licorice to enhance the reclamation status of irrigated lands through bio-reclamation, the quantitative relationship between anions and cations in moderately and severely saline soils was determined using correlation methods following laboratory analyses.